Influence of intellectual capital dimensions and government support on the performance of Islamic microfinance institutions in Malaysia - Maryam Jameelah binti Mohd Hashim (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2018)
The performance of Islamic microfinance institutions involves examining its development towards accomplishing its goals. Therefore, it is essential for Islamic microfinance institutions to determine the key challenges to maintain their operations and remaining sustainable. Islamic microfinance institutions need to focus on its intellectual capital and further prioritize their relations with government bodies and perform well so as to remain sustainable in the future. The aims of this research are to investigate the influence of intellectual capital dimensions (namely human capital, structural capital, customer capital and social capital) and the government support on the performance of Islamic microfinance institutions. This study has included knowledge as a new variable which affect the human capital (mediator) and lead to better performance of Islamic microfinance institutions. In addition, this research also focused on the impact of geographical location (moderator) of Islamic microfinance institutions towards the relationship between intellectual capital dimensions and government support on the Islamic microfinance institutions performance. A cross-sectional survey design was used to gather data from 145 managers (48% response rate) from Islamic microfinance institutions in Malaysia. To determine the sample size of the study, a judgmental sampling method was employed. Partial least square-structural equation (PLS-SEM) was used to analyse the research model. Subsequently, the research model was validated using Smart PLS 3.2.6 and proposed the study hypothesis. The findings confirmed that structural capital, customer capital, and government support positively influenced the performance of Islamic microfinance institutions, except for social capital and human capital. The result also showed that the relationship between knowledge and the performance of Islamic microfinance institutions was mediated by human capital. Further, moderation analysis showed that the geographical location of Islamic microfinance institutions moderates the relationship between intellectual capital dimensions (customer capital and structural capital), and the performance of Islamic microfinance institutions. The research model explained 72.4% of the substantial amount of variance in the performance of Islamic microfinance institutions. This research theoretically contributed to the extension of knowledge-based theory and resource-based view (RBV) in predicting the Islamic microfinance institutions performance (sustainability theory). This study is a self-reported study and is limited to selected respondents, specifically IMFI managers, and this might lead to biased perceptions towards the institutions. Therefore, future research need to focus on the different set of data collection for exogenous variables (collected from primary data) and endogenous variable (collected from secondary data) to avoid the common method bias. Overall, it can be concluded that, all dimensions of intellectual capital and government support improve the performance of Islamic microfinance institutions. Lastly, mediator and moderator do contribute to the performance of IMFIs.